Amphetamine‐type stimulant use among patients admitted to the emergency department behavioural assessment unit: Screening and referral outcomes. (6th March 2020) - Gerdtz, Marie; Yap, Celene Y.L.; Daniel, Catherine; Knott, Jonathan C.; Kelly, Peter; Innes, Andrew; Braitberg, George
Abstract: Amphetamine‐type stimulant use, including methamphetamine, amphetamine, and 3, 4‐methylenedioxymethamphetamine, is associated with a range of behavioural symptoms. Screening for amphetamine‐type stimulant use among people presenting to the emergency department with behavioural disturbance and referral to treatment has not been evaluated. The objective of this study was to determine the prevalence of amphetamine‐type stimulant use among patients admitted to a behavioural assessment unit and report referral outcomes. A prospective observational design was used. Individuals who tested positive or self‐reported amphetamine‐type stimulant use were referred to the alcohol and other drug clinician. We measured the prevalence of amphetamine‐type stimulant use in saliva and by self‐report along with rates of referral. The setting was a behavioural assessment unit located within an Australian emergency department. Admitted adults were enrolled from July to December 2017. Those who tested positive or self‐reported amphetamine‐type stimulant use were provided with harm reduction advice and offered referral. Four hundred and seventy‐two tests were performed. Fifteen were excluded due to invalid results or redundant enrolment. Of the 457 individuals, 59% were male, with a mean age of 35 years (SD 13). Fifty‐three (11.6%, 95% CI: 8.9–15.0) tested positive for amphetamine‐type stimulants. Of those with a negative test, 44 (9.6%, 95% CI: 7.3–12.7) self‐reported amphetamine‐type stimulant use in the previous 24 hours. The prevalence of amphetamine‐type stimulant use was 21.2% (95% CI: 17.7–25.2). Most accepted referral to the alcohol and other drug clinician (85.6%, 95% CI 77.2–91.2). The emergency visit represents a window of opportunity for screening for amphetamine‐type stimulant use and initiating referrals.